INTEGRASI JENDER DALAM PENGUATAN SOSIAL DAN EKONOMI KELUARGA NELAYAN PANCING TONDA (STUDI KASUS DI NEGERI URENG DAN NEGERI ASSILULU KECAMATAN LEIHITU KABUPATEN MALUKU TENGAH) - Sohilauw, Fitriyani S; Selanno, Debby A J; Lopulalan, Y (Departement of Aquatic Resources Management, Fisheries and Marine Science Faculty, Pattimura University, 2019)
Ureng and Assilulu Village have abundant potential fisheries resources. Gender has a role in utilizing fisheries resources. The research on troll lline fisher’s household was carried out at Ureng and Asslulu villages, Leihitu District, Central Maluku on December 2017 to July 2018. The objectives of this research were:1) To analyse social, economy and cultural of fishers; 2) To study the perception of fishers on equity between men and women; 3) To analyse working division between men and women to fulfill daily need, and; 4) To formulate integrated strategy to strengthening social and economy of the fisher’s household. Descriptive quantitative was used to analyse social, economy and cultural of the fisher’s household while Analyctical Hierarkhy Process was applied to analyse fisher’s activities. SWOT analysis was used to formulate strategy for gender integrated in order to strengthening social and economy of the fishers. The results showed that all fishing activities were done by men while women mostly responsible for household administration and thus have more work load than men. There were 10 strategies and 17 approaches to strengthening social and economy of the troll line fisher’s household at both villages. ABSTRAK Negeri Ureng dan Negeri Assilulu memiliki potensi sumberdaya perikanan yang melimpah. Jender memiliki peranan dalam memanfaatkan sumberdaya perikanan. Tujuan dari penelitian ini adalah: 1) menganalisis kondisi sosial, ekonomi dan budaya keluarga nelayan pancing tonda; 2) mengkaji persepsi keluarga nelayan pancing tonda tentang keadilan antara laki-laki dan perempuan; 3) menganalisis pembagian kerja antara laki-laki dan perempuan dalam rumah tangga nelayan pancing tonda dalam memenuhi kebutuhan hidup sehari-hari; dan 4) memformulasikan strategi integrasi jender bagi penguatan sosial dan ekonomi keluarga nelayan pancing tonda di Negeri Ureng dan Negeri Assilulu. Kondisi sosial, ekonomi dan budaya serta mengkaji menggunakan metode analisis data deskriptif kuantitatif. Analisis berbagai kegiatan laki-laki dan perempuan menggunakan metode Analyctical Hierarkhy Process (AHP). Strategi integrasi jender bagi penguatan sosial dan ekonomi keluarga nelayan pancing tonda dianalisis menggunakan metode analisis data SWOT. Berdasarkan hasil penelitian menunjukkan bahwa secara keseluruhan aktivitas kaum laki-laki adalah melaut, sedangkan kaum perempuan lebih banyak melakukan kegiatan mengurus rumah tangga. Berdasarkan pembagian kerja, kaum perempuan memiliki lebih banyak beban kerja. Terdapat 10 strategi yang dirumuskan serta 17 arahan bagi penguatan sosial dan ekonomi keluarga nelayan pancing tonda pada kedua negeri tersebut. Kata Kunci: Nelayan, jender, integrasi, SWOT, Negeri Ureng, Negeri Asilulu